Determination of the Toxicity of Fumonisin B1 on Male Albino Mice - Habib, Khalid A.; Al-Obaidie, Salim R.; Nayyef, Hanan J.; Khalaf, Noorulhuda (Iraqi Journal of Science, 2022)
Fumonisin B1 is a toxic compound produced by Fusarium verticillioides. Liver and kidney are the major organs considered target to FB1 toxicity that is characterized by apoptotic, necrosis, and regeneration. Thirteen local isolates of F. verticillioides isolated form maize samples that collected from local markets and silos in Baghdad. Morphological identification are occurred and confirmed by PCR and their ability to produce FB1 was detected using ELISA techniques, Thirty six male albino mice were divided into six groups. Each group orally gavaged with different concentration of FB1. After 24hours, all treated mice were examined to determine the concentration which killed half of animals and was considered as LD50, the remaining groups were scarified after two weeks of oral administration. The LD50 of FB1 was 1800ppb which demonstrated to male mice after 24h. The significant elevations in liver enzymes (AST, ALT, and ALP) and kidney functions (Creatinine, Blood urea) have shown after orally gavaging of mice with FB1 at 800 and 1200 ppb concentrations in comparison with control group. The histopathological changes in the liver, kidney and spleen of treated mice with FB1 at 800 and 1200 ppb concentrations in comparison with control group, characterized by obvious increase in degenerative changes and apoptotic cells in comparison with control group.Keywords: Fusarium verticillioides, FB1, histopathological changes, LD50